A STUDY OF CORAL REEF CONDITION AND CORAL REEF FISH BIODIVERSITY IN THE WATERS OF LEMBEH STRAIT - Hamel S.; Ratela J.; Taulandani S.; Ticoalu D. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
Lembeh Strait marine tourism area in Bitung City of North Sulawesi province has many diving spots because of its specific and unique coral reef. However, it is very seriously threatened by degradation, so it needs a study to monitor the level of damage so that the recovery process can be obtained. This study aimed at determining the distribution of the percentage of the condition of coral reefs and fish biodiversity throughout the Lembeh Strait. This research was carried out in the northern waters of the Lembeh Strait: Mawali waters, Serena Island waters, Tandurusa waters, and Makawidey waters (3-5 m depth). Data were collected by diving using the Underwater Photo Transect (UPT) and Underwater Visual Census (UVS) methods in the transect area of 350 m2. The results of the study showed that the condition of coral in the Lembeh Strait had seriously degraded with a mean health level of 23.07% and a damage rate of 76.3%. Generally, the coral reef biodiversity is still relatively low but still warn to be vigilant. The environmental factors still support the survival of coral reefs.